Overview of Social Interaction and Quality of Life of the Elderly in Pasinggangan Village, Banyumas - Eva Nurhayati; Kris Linggardini (UM Purwokerto Press, 2026)
The elderly population is vulnerable to a decline in social interaction and quality of life due to physical, psychological, and social changes associated with the aging process. Maintaining social engagement is essential to support well-being and life satisfaction among older adults. This study used a descriptive quantitative design with a survey approach. The research was conducted in Pasinggangan Village, Banyumas Regency, involving 52 elderly respondents selected using random sampling based on the Slovin formula. Data were collected using questionnaires measuring social interaction and quality of life and analyzed using univariate descriptive statistics. The majority of respondents were aged 60–74 years (75%) and female (76.9%), with hypertension being the most common health condition (21.2%). Most elderly respondents demonstrated good social interaction (73.1%), while 23.1% had moderate interaction and 3.8% had poor interaction. Regarding quality of life, 82.7% had moderate quality of life, 15.4% good, and 1.9% poor. The findings indicate that most elderly individuals in Pasinggangan Village have relatively active social interaction and a moderately good quality of life. Strengthening social support and community engagement is essential to improve elderly well-being.